Coulomb gauge quark model, vacuum condensates and high density quark matter - Panda, P. K.; Krein, G. (American Institute of Physics (AIP), 2002)
We consider here a Coulomb gauge quark model which includes an explicit construct for a nontrivial vacuum structure in QCD at finite density. Non-perturbative renormalization of ultraviolet diverges is performed by adding counterterms. The equation of state for u and d quark matter at zero temperature is calculated in the Hartree-Fock approximation.